2020
DOI: 10.1038/s41398-020-00943-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced axonal caliber and structural changes in a rat model of Fragile X syndrome with a deletion of a K-Homology domain of Fmr1

Abstract: Fragile X syndrome (FXS) is a neurodevelopmental disorder that is caused by mutations in the FMR1 gene. Neuroanatomical alterations have been reported in both male and female individuals with FXS, yet the morphological underpinnings of these alterations have not been elucidated. In the current study, we found structural changes in both male and female rats that model FXS, some of which are similarly impaired in both sexes, including the superior colliculus and periaqueductal gray, and others that show sex-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…An abnormal increase of WM maturation was observed in an adolescent model of compulsive checking behavior [ 76 ], in selectively bred ASD/ADHD-like behavior rats [ 77 ], and in animals with repetitive traumatic brain injury (TBI) that showed impulsivity [ 78 ]. In line with our result, some studies have shown an increase in CC in an adolescent model of compulsive checking behavior [ 76 ], in selectively bred ASD/ADHD-like behavior rats [ 77 ], and in a female rat model of Fragile X syndrome characterized by autistic behaviors [ 79 ]. Moreover, OCD-like behavior mice exhibited increased c-fos expression in the AC ([ 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…An abnormal increase of WM maturation was observed in an adolescent model of compulsive checking behavior [ 76 ], in selectively bred ASD/ADHD-like behavior rats [ 77 ], and in animals with repetitive traumatic brain injury (TBI) that showed impulsivity [ 78 ]. In line with our result, some studies have shown an increase in CC in an adolescent model of compulsive checking behavior [ 76 ], in selectively bred ASD/ADHD-like behavior rats [ 77 ], and in a female rat model of Fragile X syndrome characterized by autistic behaviors [ 79 ]. Moreover, OCD-like behavior mice exhibited increased c-fos expression in the AC ([ 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, axons with larger diameter show a detectable contrast according to our simulations, see Supplementary Materials . Despite this limitation, since large axons are found preferentially in specific pathways, their absence in the expected pathways, or abnormal presence in unexpected pathways can disclose the neural basis of specific neurological or psychiatric pathologies (DeLuca et al, 2004 ; Zikopoulos and Barbas, 2013 ; Huang et al, 2016 ; Judson et al, 2017 ; Golden et al, 2020 ) and, possibly, of individual skills (de Manzano and Ullén, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the regions that were reduced in volume, the superior and inferior colliculi and the thalamus, are involved in sensory processing, suggesting a potential locus for the sensory deficits often documented in PMS and the rat model (De Rubeis et al, 2018 ; Droogmans et al, 2020 ; Engineer et al, 2018 ). Interestingly, we recently reported similar structural alterations in another rat model of a monogenic cause of ASD, Fragile X syndrome, using the same imaging techniques and parameters (Golden et al, 2020 ), establishing the potential for commonality across syndromes. The relationship between the structure of these regions and their functional consequences should be further investigated in rodent models of ASD.…”
Section: Discussionmentioning
confidence: 56%